2015
DOI: 10.1098/rspb.2015.1111
|View full text |Cite
|
Sign up to set email alerts
|

Plant defences against ants provide a pathway to social parasitism in butterflies

Abstract: Understanding the chemical cues and gene expressions that mediate herbivore–host-plant and parasite–host interactions can elucidate the ecological costs and benefits accruing to different partners in tight-knit community modules, and may reveal unexpected complexities. We investigated the exploitation of sequential hosts by the phytophagous–predaceous butterfly Maculinea arion, whose larvae initially feed on Origanum vulgare flowerheads before switching to parasitize Myrmica ant colonies for their main period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…Such differences among the essential oils could be due to the density of oil glands associated with the plant tissues, changes in the growth environment as the plant develops, and/or a shifting distribution of carbohydrates to plant growth and development as opposed to essential oil synthesis. For example, several plants alter essential oil production to attract pollinators and inhibit pests and herbivores (Patricelli et al, ; Hosni, Msaada, Taârit, & Marzouk, ; Figueiredo, Barroso, Pedro, & Scheffer, ). Earlier studies (Crocoll, Asbach, Novak, Gershenzon, & Degenhardt, ; Werker, Putievsky, & Ravid, ; Giuliani, Maggi, Papa, Maleci Bini, ) indicated that the glandular trichomes and percentage of essential oil in oregano are primarily concentrated in the flowers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such differences among the essential oils could be due to the density of oil glands associated with the plant tissues, changes in the growth environment as the plant develops, and/or a shifting distribution of carbohydrates to plant growth and development as opposed to essential oil synthesis. For example, several plants alter essential oil production to attract pollinators and inhibit pests and herbivores (Patricelli et al, ; Hosni, Msaada, Taârit, & Marzouk, ; Figueiredo, Barroso, Pedro, & Scheffer, ). Earlier studies (Crocoll, Asbach, Novak, Gershenzon, & Degenhardt, ; Werker, Putievsky, & Ravid, ; Giuliani, Maggi, Papa, Maleci Bini, ) indicated that the glandular trichomes and percentage of essential oil in oregano are primarily concentrated in the flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol has also antifungal and insecticidal properties (Mendes, ; Patricelli et al, ; Tabari, Youssefi, Maggi, & Benelli, ) and, due to the fact that plants are more sensitive to herbivores and disease at an early vegetative stage, high amounts of carvacrol could be functioning as an allomone. Increasing the carvacrol content in flowers and at the flowering stage demonstrates the role of this phenolic monoterpene as a kairomone (Patricelli et al, ). The monoterpene hydrocarbons p‐ cymene and γ‐terpinene function as precursors for carvacrol and thymol (Crocoll et al, ; Vitali et al, ) and thus their levels decrease as the level of carvacrol increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility could be the detection of plant volatiles by gravid females, as has been demonstrated for P. arion by Patricelli et al. (): Origanum host plants produce the monoterpenoid carvacrol when ants disturb their roots. Myrmica ants are much more resistant to carvacrol than other ant species, giving them an enemy free space in the Origanum roots to occupy.…”
Section: Discussionmentioning
confidence: 97%
“…In general, this has concurred to underestimate the indirect cues provided by the “information web” (e.g., CHCs), which covers and is interwoven to the “food web” [151]. There are a few examples of studies considering all possible relationships, energy fluxes, exchange of signals occurring among all the organisms involved in multitrophic interactions (e.g., [152,153]), but these are almost absent in the case of surveys involving ant–butterfly–plant systems (but see [154]). It is indeed necessary to take into account the overall variation of associated costs and benefits of these systems to fully comprehend their co-evolutionary dynamics and the whole array of possible outcomes ([151,155] and references therein).…”
Section: Discussionmentioning
confidence: 99%